The NF-κB Transcription Factor c-Rel Modulates Group 2 Innate Lymphoid Cell Effector Functions and Drives Allergic Airway Inflammation - Mindt, Barbara C.; Krisna, Sai Sakktee; Duerr, Claudia U.; Mancini, Mathieu; Richer, Lara; Vidal, Silvia M.; Gerondakis, Steven; Langlais, David; Fritz, Jörg H. (Frontiers in Immunology, 2021)
Group 2 innate lymphoid cells (ILC2s) play a key role in the initiation and orchestration of early type 2 immune responses. Upon tissue damage, ILC2s are activated by alarmins such as IL-33 and rapidly secrete large amounts of type 2 signature cytokines. ILC2 activation is governed by a network of transcriptional regulators including nuclear factor (NF)-κB family transcription factors. While it is known that activating IL-33 receptor signaling results in downstream NF-κB activation, the underlying molecular mechanisms remain elusive. Here we found that the NF-κB subunit c-Rel is required to mount effective innate pulmonary type 2 immune responses. IL-33-mediated activation of ILC2s in vitro as well as in vivo was found to induce c-Rel mRNA and protein expression. In addition, we demonstrate that IL-33-mediated activation of ILC2s leads to nuclear translocation of c-Rel in pulmonary ILC2s. Although c-Rel was found to be a critical mediator of innate pulmonary type 2 immune responses, ILC2-intrinsic deficiency of c-Rel did neither impact the developmental capacity of ILC2 nor affect homeostatic numbers of lung-resident ILC2s at steady state. Moreover, we demonstrate that ILC2-intrinsic deficiency of c-Rel does not alter the proliferative capacity of ILC2s upon IL-33-mediated activation in vitro and that c-Rel-deficiency does not result in impaired expression of key stimulatory receptors and the type 2 signature cytokines IL-5 and IL-13. Collectively our data using Rel-/- mice suggests that c-Rel promotes acute ILC2-driven allergic airway inflammation and suggests that c-Rel may contribute to the pathophysiology of ILC2-mediated allergic airway disease. It thereby represents a promising target for the treatment of allergic asthma and evaluating the effect of established c-Rel inhibitors in this context would be of great clinical interest.